The Implication of Piaget’s Cognitive Theory on Indonesian Learning through Bigbook - Cahyaningsih, Esty; Santosa, Sedya (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
At the madrasah ibtidaiyah level, Indonesian language lessons are very important in enabling students to comprehend reading concepts, use and reflect on written reading. The research method employed a qualitative case study method. This research was carried out at the NU Tarbiyatuth Thullab madrasah ibtidaiyah, using data triangulation techniques (interviews, observation and documentation). The results of this research show that Indonesian language learning at MI NU Tarbiyatuth Thullab uses bigbook media to deepen students' comprehension. Additionally, teachers also apply the theory of student cognitive development through Jean Piaget's theory. The benefits of using bigbook and applying Piaget's theory help teachers in developing student’s reading abilities. Through the application of Piaget's theory, teachers could understand students' cognitive capabilities based on their developmental ages. Through bigbook learning media, students become more enthusiastic and interested as the materials contained interesting stories.